2004
DOI: 10.1002/dmrr.449
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal involvement in patients with diabetes mellitus

Abstract: Studies on skeletal involvement in patients with diabetes mellitus have generated conflicting results, largely because of the pathogenetic complexity of the condition. Several mechanisms may contribute to skeletal damage, including the increased urinary excretion coupled with the lower intestinal absorption of calcium, the inappropriate homeostatic response in terms of parathyroid hormone secretion, and also the complex alteration of vitamin D regulation. Decreased or increased insulin and IGF-1 concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
145
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(150 citation statements)
references
References 114 publications
3
145
0
2
Order By: Relevance
“…Subjects reporting diabetes also perceived the lowest rate of change on the GROC (2.33). This finding is in agreement with several studies that reported that diabetes reduces BMD, which puts individuals with diabetes at a higher risk for a slower recovery rate [5,7,29].…”
Section: Discussionsupporting
confidence: 93%
“…Subjects reporting diabetes also perceived the lowest rate of change on the GROC (2.33). This finding is in agreement with several studies that reported that diabetes reduces BMD, which puts individuals with diabetes at a higher risk for a slower recovery rate [5,7,29].…”
Section: Discussionsupporting
confidence: 93%
“…Type I diabetes mellitus negatively alters the mechanical and biologic properties of bone [3,22] and has been associated with an increased risk of complications with fracture healing, including delayed union, wound necrosis, and increased incidence of infection [6,8,23,25,28]. An intervention that would overcome this inhibition of fracture healing would be useful clinically.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these complications result from progressive small vessel arterial disease and peripheral neuropathy that develop with time and are largely untreatable [19,29]. Type I diabetes mellitus alters the mechanical and biologic properties of bone [3,22]. Impairment of histomorphometric, cellular, and biochemical indicators of bone formation, like osteocalcin have been linked to diabetes mellitus [15,27,32].…”
Section: Introductionmentioning
confidence: 99%
“…Other parameters may also be affected including AGE-inhibited proliferation and differentiation (33). Although not formally linked, it is possible that problems with fracture repair associated with type 1 diabetes (10,14,41) are directly or indirectly related to the effects of AGEs on osteoblasts. Since enhanced osteoblast apoptosis may represent an important mechanism through which bone formation is limited (19) we investigated the capacity of glycated collagen to stimulate apoptosis of osteoblastic cells and investigated the apoptotic pathways that were stimulated.…”
Section: Introductionmentioning
confidence: 99%